1999
DOI: 10.1038/sj.bjc.6690493
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour activity in vitro and in vivo of selective differentiating agents containing hydroxamate

Abstract: Summary A series of hydroxamates, which are not metalloprotease inhibitors, have been found to be selectively toxic to a range of transformed and human tumour cells without killing normal cells (fibroblasts, melanocytes) at the same concentrations. Within 24 h of treatment, drug action is characterized by morphological reversion of tumour cells to a more normal phenotype (dendritic morphology), and rapid and reversible acetylation of histone H4 in both tumour and normal cells. Two hydroxamates inhibited growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 28 publications
1
69
0
Order By: Relevance
“…Suberoylanilide hydroxamic acid is in phase I and II clinical trials for the treatment of various cancers and has shown anticancer activity at doses that are well tolerated by patients (11,12). These preclinical results and the clinical trials show that suberoylanilide hydroxamic acid targets transformed cells in preference to normal cells (9).…”
Section: Discussionmentioning
confidence: 71%
“…Suberoylanilide hydroxamic acid is in phase I and II clinical trials for the treatment of various cancers and has shown anticancer activity at doses that are well tolerated by patients (11,12). These preclinical results and the clinical trials show that suberoylanilide hydroxamic acid targets transformed cells in preference to normal cells (9).…”
Section: Discussionmentioning
confidence: 71%
“…Here, we have demonstrated that HDIs are cytotoxic to both proliferating and nonproliferating cells, with little loss of potency although there is a delay in the onset of cell death. We have previously demonstrated that HDIs have tumour-selective cytotoxicity (Qiu et al, 2000;Qiu et al, 1999). Thus, this class of drugs has many of the characteristics desired in an anticancer drug, selective cytotoxicity and the ability to kill both actively proliferating and nonproliferating tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SAHA induces apoptosis in some cancer cells, but not in equivalent normal cells, when combined with either X-rays or carbon ions. It has been postulated that this unexpected finding is related to differing transcriptional regulation between cancer and normal cells (Qiu et al 1999;Minucci and Pelicci 2006). In particular the cyclin-dependent kinase inhibitor 1 gene (p21 WAF1 ), which in general prevents proliferation, is suppressed in many tumour cells but is upregulated by SAHA resulting in cell death (Gui et al 2004).…”
Section: Introductionmentioning
confidence: 99%